Performance indicators for lifecycle process of public private partnership (PPP) projects in Malaysia - Ismail, Suhaiza; Mohamad, Rosnani; Mohd Said, Julia (Emerald Publishing Limited, 2021)
Purpose – This paper has two objectives. The first objective is to examine the important performance indicators of the lifecycle process of public private partnership (PPP) projects. The second objective is to investigate the difference in the perception of the importance of the performance indicators between the public and private sectors. Design/methodology/approach – To achieve the research objectives, the study used a questionnaire survey. The questionnaire was distributed via postal mail to officers of government departments and private sector companies who may have been involved in PPP projects. A total of 237 completed questionnaires were received, representing a 51.52% response rate. To examine the importance of performance indicators, the descriptive statistical tests of mean, standard deviation and mean score ranking were used. Independent t-tests were conducted to investigate the differences in the perceptions of the importance of performance indicators between the two respondent groups. Findings – The findings show that all the 16 performance indicators are perceived as important and very important. The top five important performance indicators for a PPP project lifecycle process are “Time management”, “Contractual management”, “Cost management”, “Safety management” and “Effective risk management system”, while “stress or conflicts management”is the least important. In terms of the differences in the perception of the public and private sector groups, the results indicate that four indicators (“environment protection”, “cost management”, “effective risk management system” and “good work environment”), show a significant statistical difference between the perception of the public and the private sector respondents. Originality/value –This study offers empirical evidence on key performance indicators for a PPP project that are crucial throughout its lifecycle as perceived by two key parties in a PPP contract, i.e. the public and the private sectors.